Effect of four irrigation doses and four varieties on cotton bolls component, lint ratio and quality: cotton irrigation and quality - Darawsheh, Mohammed K.; Kakabouki, Ioanna; Folina, Antigolena; Karydogianni, Stella; Katsenios, Nikolaos; Zisi, Charikleia (Journal of Aridland Agriculture, 2020)
Cotton is an industrial crop grown both in the north and in the Southern hemisphere and is one of the most profitable crops. Water is the resource that will be the most limited, especially for agriculture in the coming years. Irrigation availability is a critical factor in growing cotton in hot and dry climates. The experiments were performed in central Greece, in Palamas of the Karditsa region, for two years (2015-2016). The treatments were four different irrigation regimes, where IRR. 2 and IRR. 4 were deficient irrigations, IRR. 6, was a sufficient and IRR. 8, were overflow. Four varieties of cotton (Dp 419, Campo, Andromeda, Lider) were used where the effects of irrigation on cotton boll characteristics were recorded. The measurements made concerned the agronomic as well as the qualitative characteristics of the cotton bolls such as lint proportion, seed percentage, oil content, oil yield and micronaire. The oil content had positive correlation with the lint proportion and negative correlation with the seed percentage. In the both years of experiments the IRR. 2 and IRR. 8, irrigation regimes had negative effects while IRR. 4 and IRR. 6 had positive effects. Also among the varieties, Andromeda and Lider were the ones that stood out in both years.